2014
DOI: 10.18632/oncotarget.1936
|View full text |Cite
|
Sign up to set email alerts
|

Expression of stemness genes in primary breast cancer tissues: the role of SOX2 as a prognostic marker for detection of early recurrence

Abstract: The events leading to breast cancer (BC) progression or recurrence are not completely understood and new prognostic markers aiming at identifying high risk-patients and to develop suitable therapy are highly demanded. Experimental evidences found in cancer cells a deregulated expression of some genes involved in governance of stem cell properties and demonstrated a relationship between stemness genes overexpression and poorly differentiated BC subtypes.In the present study 140 primary invasive BC specimens wer… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

5
42
2

Year Published

2016
2016
2022
2022

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 41 publications
(49 citation statements)
references
References 48 publications
5
42
2
Order By: Relevance
“…However, contrary to previous studies [9, 22], it was not associated with clinical outcome of the patients. This discrepancy may be associated with differences in sample platform, criteria for scoring and cutoff points for positive staining.…”
Section: Discussioncontrasting
confidence: 99%
“…However, contrary to previous studies [9, 22], it was not associated with clinical outcome of the patients. This discrepancy may be associated with differences in sample platform, criteria for scoring and cutoff points for positive staining.…”
Section: Discussioncontrasting
confidence: 99%
“…Positive correlations between SOX2 expression and disease stage and tumor differentiation have been reported, and SOX2 expression has also been associated with the poor clinical outcome of ovarian cancer . Similarly, SOX2 was also found to be a prognostic marker for detecting the early recurrence of breast cancer . In our study, we also found that SOX2 protein expression was closely associated with chemo‐resistance and poor prognosis in EOC patients, which was consistent with the previous studies.…”
Section: Discussionsupporting
confidence: 92%
“…Moreover, SOX2 protein has been assessed as a diagnostic marker and therapeutic target for multiple cancer treatments [6870]. Our results suggest that high levels of SOX2 protein are associated with poor prognosis of breast cancer.…”
Section: Discussionmentioning
confidence: 69%